Differential Modulation of Nitric Oxide Synthases in Aging: Therapeutic Opportunities - Cau, Stêfany B.; Carneiro, Fernando S.; Tostes, Rita (Frontiers in Physiology, 2012)
Vascular aging is the term that describes the structural and functional disturbances of the vasculature with advancing aging. The molecular mechanisms of aging-associated endothelial dysfunction are complex, but reduced nitric oxide (NO) bioavailability and altered vascular expression and activity of NO synthase (NOS) enzymes have been implicated as major players. Impaired vascular relaxation in aging has been attributed to reduced endothelial NOS (eNOS)-derived NO, while increased inducible NOS (iNOS) expression seems to account for nitrosative stress and disrupted vascular homeostasis. Although eNOS is considered the main source of NO in the vascular endothelium, neuronal NOS (nNOS) also contributes to endothelial cells-derived NO, a mechanism that is reduced in aging. Pharmacological modulation of NO generation and expression/activity of NOS isoforms may represent a therapeutic alternative to prevent the progression of cardiovascular diseases. Accordingly, this review will focus on drugs that modulate NO bioavailability, such as nitrite anions and NO-releasing non-steroidal anti-inflammatory drugs, hormones (dehydroepiandrosterone and estrogen), statins, resveratrol and folic acid, since they may be useful to treat/to prevent aging-associated vascular dysfunction. The impact of these therapies on life quality in elderly and longevity will be discussed.